Perbandingan Laju Pertumbuhan Tukik Penyu Lekang (Lepidochelys olivacea) dengan Pemberian Pakan Ikan Tongkol, Udang Rebon Kering dan Pakan Campuran - Lazaren, Cornelia Coraima; Karang, I Wayan Gede Astawa; Faiqoh, Elok (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018), 2017)
The population of olive ridley has declined in Indonesia, so that efforts are needed to preserve this turtle population through conservation. In conservation of olive ridley, the selection of the precise feed will affect for a good growth. Feed that has high protein content one of them is dried rebon shrimp and tongkol fish. The utilization of feed from dried rebon shrimp and tongkol fish, especially mix feed of these two feeds for olive ridley baby is still very limited information. This research aims to determine the comparison growth rate of olive ridley with a feeding of tongkol fish, dried rebon shrimp and mixed feed also to know the percentage of feed efficiency. The research was conducted for six weeks at the conservation center TCEC Serangan, Bali. The design method used was Completely Randomized Design (CDR) with one control and three treatments, each treatment getting five repetitions. ANOVA analysis was used to analyze the mean differences between groups and the calculation of feed efficiency was performed to see the percentage of feed that was most efficient in the body of the hatch. The results showed different feeds gave different growth rates. The high protein on mixed feeds has produced the highest growth rates compared with dried rebon shrimp and tongkol fish feed. Similarly, the percentage efficiency of mixed feed is more efficient compared with dried rebon shrimp and tongkol fish feed .